Consumer preferences concerning potentially unsafe food - Chatten, Victoria; BCIT School of Health Sciences, Environmental Health; Sidhu, Bobby; McIntyre, Lorraine (BCIT Environmental Public Health Journal, 2014)
BACKGROUND: Recent studies have shown that the reasons behind consumers’ preferences towards certain food products are extremely dynamic. Organic foods, raw milk products and bottled water are a few products discussed in this paper that have gone under debate regarding their safety versus their perceived health benefits. METHODS: Over 100 people participated in an exclusively online self-administered questionnaire. The questionnaire was publicized through both email and social media. Participants responded to questions regarding their food preferences of a variety of food types. RESULTS: It was found that there was a statistically significant association between education and preferences towards both milk products and organic/non-organic food products. No other demographic (setting, gender, age) were found to be associated with food preferences. It was also found that all food preferences were associated with the reasoning for that specific food preference, with the exception of cut/whole fruit. CONCLUSION: The association between food preferences and its reasoning concludes that consumers who prefer opposing products do so for extremely different reasons. Consumers that prefer the more risky food products mainly do so for taste and potential health benefits. Public health officials need to ensure that consumers that prefer riskier products thoroughly understand the risks, so that they themselves can then truly compare the benefits of taste or perceived “healthiness” with the consequences of potential contamination and illness.